Transepidermal water loss increases during murine food anaphylaxis and reflects reaction severity - Woerner, Benjamin N.; Abbo, Joseph; Wang, Allison; Donahue, Melanie K.; Hines, Judy; O’Konek, Jessica; Hogan, Simon P.; Baker, James R.; Schuler, Charles F. (Frontiers in Immunology, 2025)
BackgroundAn increase in transepidermal water loss (TEWL) presages food anaphylaxis in allergic humans during oral food challenges. We sought to determine whether similar TEWL changes occur in mouse food anaphylaxis models.MethodsUsing a Tewameter™ Nano, a mouse-compatible device, TEWL measurements were conducted on the ear, paw, and abdomen of BALB/c mice. Because of the highest measurement reproducibility, the ear was selected for use in the study. Baseline TEWL measurements under varied conditions were evaluated. Histamine injections were given to evaluate a non-IgE-mediated reaction. Two IgE-based models of food anaphylaxis were utilized: (1) passive systemic anaphylaxis (PSA) with dinitrophenyl (DNP)-IgE sensitization and DNP-albumin challenge, and (2) active systemic anaphylaxis (ASA) with ovalbumin-alum immunization followed by ovalbumin challenges. Core temperature, reaction severity score, diarrhea, and TEWL were recorded. MCPT-1 was measured as a mast cell activation correlate.ResultsTEWL was reproducibly measured on the ear (17.7 g/m2/h) and showed no baseline differences with time, sex, device used, oral gavage, or intravenous injection. TEWL increased during histamine (5.73 g/m2/h), PSA (3.46 g/m2/h), and ASA (3.61 g/m2/h) challenges. TEWL correlated with reaction severity across conditions and with core temperature change in PSA and ASA challenges. TEWL increased significantly for all models, whereas other markers such as reaction severity and temperature change varied by model utilized.ConclusionTEWL is reliably measured on the mouse ear. TEWL increased under varied reaction conditions, and the stimulus used did not alter results. TEWL offers a novel, real-time, objective, and noninvasive measure of murine food anaphylaxis that corresponds to human pathophysiology.